1997
DOI: 10.1046/j.1365-2567.1997.00325.x
|View full text |Cite
|
Sign up to set email alerts
|

Extracorporeal photochemotherapy restores Th1/Th2 imbalance in patients with early stage cutaneous T‐cell lymphoma

Abstract: SUMMARYExtracorporeal photochemotherapy ( ECP) has been shown to be a potent activator of peripheral blood macrophages because it causes a marked release of macrophage-dependent proinflammatory cytokines, and it is therefore currently considered to be a safe and non-toxic immunomodulatory treatment. On this basis we studied the function of peripheral blood mononuclear cells (PBMC ) in eight patients with early stage (Ib) cutaneous T-cell lymphoma (CTCL), before and 1 year after ECP, together with their clinica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
83
1
10

Year Published

1998
1998
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 113 publications
(94 citation statements)
references
References 28 publications
0
83
1
10
Order By: Relevance
“…26 ECP can also affect TH1/TH2 ratios. 27 However, our studies using a novel single cell cytokine assay showed no effect of ECP on TH1/TH2 ratios in patients with chronic cutaneous GVHD. 28,29 Our results indicate that ECP can benefit patients with cutaneous and mucosal chronic GVHD who have failed to improve on first-and second-line therapies.…”
Section: Discussionmentioning
confidence: 62%
“…26 ECP can also affect TH1/TH2 ratios. 27 However, our studies using a novel single cell cytokine assay showed no effect of ECP on TH1/TH2 ratios in patients with chronic cutaneous GVHD. 28,29 Our results indicate that ECP can benefit patients with cutaneous and mucosal chronic GVHD who have failed to improve on first-and second-line therapies.…”
Section: Discussionmentioning
confidence: 62%
“…In the context of CTCL, the restoration of Th1 cytokine secretion increases IL-12 production by monocytes, which might subsequently inhibit Th2 cytokine secreting cells that are believed to be responsible for the clinical manifestations of CTCL. 35 While monocytes appear to be resistant to the apoptotic effects of ECP, the induction of TNF-␣ secretion by photoactivated monocytes facilitates lymphocyte apoptosis. 36 Further, photoactivation of monocytes by ECP has also been shown to enhance their differentiation into CD83 + CD36 + dendritic cells capable of phagocytosing the apoptotic T cells.…”
Section: Effects Of Ecp On Lymphocytes Monocytes and Dendritic Cellsmentioning
confidence: 99%
“…DiRenzo u. Mitarb. konnten zeigen, dass es bei Patienten mit kutanem T-Zell-Lymphom im Stadium Ib nach 1-jähriger ECP-Therapie nicht nur zur Erhöhung der CD36 + -Monozyten im peripheren Blut kommt, sondern auch zur Angleichung des Zytokin-Reaktionsprofils von peripheren Blutlymphozyten auf Stimulation mit Phytohämagglutinin in vitro im Vergleich zu gesunden Kontrollen [35]. Diese Effekte wurden dahingehend interpretiert, dass die Balance der pathologischen Th1/Th2-Immunantwort bei Patienten mit CTCL durch die ECP-Therapie wiederhergestellt wird.…”
Section: Weitere Immunmodulatorische Effekteunclassified